2021
DOI: 10.3390/agriculture11111177
|View full text |Cite
|
Sign up to set email alerts
|

Effective Management of Cucumber Powdery Mildew with Essential Oils

Abstract: This research evaluated the efficacy of essential oils in the management of cucumber powdery mildew. Essential oils of lemongrass, lemon, thyme, peppermint, abundance blend, purification blend, and thieves blend were tested in vitro and under greenhouse conditions in two separate experiments. The effects of essential oils were tested against powdery mildew disease at concentrations of 1.0–2.5 mL/L, and the consequent impact of the oils on plant growth was evaluated. Powdery mildew fungus, Podosphaera xanthii, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…phyllosphere microbial community while achieving the same control efficacy as the synthetic fungicide tebuconazole. Many environmentally friendly control agents have been tested for cucumber, and the results suggest no significant differences in efficacy relative to synthetic fungicides [12,15,16]. Consistent with these previous studies, we observed that both the plant elicitor NPA and the ancient plant disease control agent sulfur effectively controlled powdery mildew on cucumber and displayed no significant differences from tebuconazole.…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…phyllosphere microbial community while achieving the same control efficacy as the synthetic fungicide tebuconazole. Many environmentally friendly control agents have been tested for cucumber, and the results suggest no significant differences in efficacy relative to synthetic fungicides [12,15,16]. Consistent with these previous studies, we observed that both the plant elicitor NPA and the ancient plant disease control agent sulfur effectively controlled powdery mildew on cucumber and displayed no significant differences from tebuconazole.…”
Section: Plos Onesupporting
confidence: 89%
“…At present, the use of environmentally friendly fungicides has been proposed as a substitute for the application of synthetic fungicides, especially for organic farming. The environmentally friendly fungicides that control cucumber powdery mildew include neutralized phosphorous acid (NPA), sulfur, potassium bicarbonate, emulsified oil [12], and other biological control agents. NPA is an elicitor of the plant defense response [13] and has been suggested to effectively control powdery mildew caused by P. xanthii [14][15][16] and Oidium sp.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, there has been an increase in the quest for plant extracts with anti-ascomycete activity. These studies have shown that plant extracts are effective against S. fuliginea, the fungal pathogen that causes the powdery mildew disease that affects Cucurbitaceae (Al Surhanee 2013;Guginski-Piva et al 2015;Abdu-Allaha and Abo-Elyousr 2017;El-Ghanam et al 2018;Mostafa et al 2021a) There are several ways that plants defend themselves from diseases, such as phenolic complexes, which are secondary plant metabolites. These substances can be found in the root, rhizome, shoot, leaf, and flower of the plant (Houssien et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous scientists have hypothesized that plant pathogens lead to an increase in phenolic chemicals and related defense enzymes in plants (Bhattacharya et al 2010;Baka et al 2013;Mianabadi et al 2015;Mostafa et al 2021aMostafa et al , b 2022. According to some researchers, spraying crops with a lot of plant extracts increased agricultural production (Mvumi et al 2013;Elzaawely et al 2017;Bello et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It has a favorable flavor and texture, as well as medicinal values, including antioxidant ability, antimicrobial activity, and the ability to lower glycemic levels. Eating cucumber may be beneficial in improving immunity, boosting the metabolism, and reducing the risks of cancers [2][3][4]. Therefore, it is often eaten both fresh, e.g., in salads, and processed or preserved, e.g., as pickles.…”
Section: Introductionmentioning
confidence: 99%